Peningkatan kinerja instansi melalui efikasi diri dan komunikasi interpersonal serta kerjasama tim sebagai pemediasi pada badan pegelola pajak dan retribusi daerah kota Medan - Attyka Dewi Tri W; H. M. Hermansyur; Annisha Suvero Suyar (Insight Management Journal, 2021)
This study aims to determine the effect of self-efficacy and interpersonal communication on team collaboration at the Medan City Tax and Retribution Management Agency partially. This is to find out whether organizational support moderates the effect of self-efficacy and interpersonal communication on improving agency performance in the Medan City Regional Tax and Retribution Management Agency. The total population in this study amounted to 249 people, and using the Slovin formula obtained a sample of 153 people. The analysis technique used is multiple linear regression. The results showed that self-efficacy had a significant effect on the performance of agencies in the Medan City Regional Tax and Retribution Management Agency. Interpersonal communication has a significant effect on the performance of agencies in the Medan City Regional Tax and Retribution Management Agency. Self-efficacy has no effect on teamwork at the Medan City Regional Tax and Retribution Management Agency. Interpersonal communication has a significant effect on teamwork at the Medan City Regional Tax and Retribution Management Agency. Teamwork has no effect on the performance of agencies in the Medan City Regional Tax and Retribution Management Agency.